Politik dan Ekonomi di Dua Kota: Baubau dan Kendari pada tahun 1950an–1960an - La Ode Rabani; Bambang Purwanto; Sri Margana (Universitas Airlangga, 2020)
This article explains the implications of political-economic shock on the development of two towns; Baubau and Kendari in the 1950s to 1960s. Indonesia in the 1950s general and especially Southeast Sulawesi were politically and economically unstable. This situation happened because the country is still on the stage of finding a balance and political and economic consolidation has not reached the point of equilibrium. As a result, political shock occurred in certain areas due to differences in views, including in South Sulawesi and Southeast Sulawesi. One of the political disturbances that influenced the development of the towns was the DI / TII rebellion in the 1950s. One of the effects of political turmoil in two cities, Buton and Kendari, is the flow of rural populations into towns. Military operations to eliminate security disturbances in the towns of Baubau and Kendari support the improvement of infrastructure for access to the town and expand morphology of towns. The author examines, reads, and examines documents archives carefully in South and Southeast Sulawesi. The facts in the archives show that political and economic shocks have a good effect on one thing and not good on another side. The events of political turmoil in Southeast Sulawesi provide important lessons and knowledge about the other side of political and economic shocks.